Inflammatory roles of P-selectin. - Lorant, D E (1993)
Polymorphonuclear leukocytes (PMNs) bind rapidly and reversibly to endothelial cells induced to express P-selectin, a glycoprotein that mediates adhesive intercellular interactions. In addition, PMNs adherent to endothelium expressing P-selectin demonstrate an intracellular Ca2+ transient, functionally up-regulate beta-2-integrins (CD11/CD18 glycoproteins), become polarized in shape, and are primed for enhanced degranulation when subsequently stimulated with chemotactic factors. However, P-selectin induces none of these responses directly when used alone, when incorporated into model membranes, or when expressed by transfected cells. The absence of direct activation of the PMNs is not due to competing antiinflammatory effects of P-selectin; instead, purified P-selectin and P-selectin in membranes support agonist-stimulated PMN responses. Furthermore, tethering of PMNs to endothelial surfaces by P-selectin is required for priming to occur efficiently, as shown by experiments with blocking monoclonal antibodies. The priming event is directly mediated by the signaling molecule, platelet-activating factor (PAF), and is inhibited by blocking the PAF receptor on PMNs. Thus, P-selectin and PAF are components of an adhesion and activation cascade, but have distinct roles: P-selectin tethers and captures the PMN, whereas PAF mediates juxtacrine activation. In vivo, selectins may facilitate interaction of target cells with membrane-bound molecules that send intercellular signals, in addition to mediating rolling of leukocytes and other adhesive functions.